Towards a Morphology of Critique: An Attempt to Classify Approaches to Literary Criticism - Martin Suryajaya (POETIKA, 2023)
This study examines the possibility of classifying approaches to literary criticism so that each critical position can be mapped to other critical positions. This article is not an application of a literary criticism approach to reading a particular literary work but an attempt to map the relationships between approaches to literary criticism so that the issues raised here are theoretical and methodological rather than practical. This research offers another alternative: a comprehensive and valuable classification can be obtained by classifying the formal elements of reading practice rather than the theme. The method used here is a morphological study in the spirit of Vladimir Propp (2009) applied to the modality of reading to overcome the limitations of thematic classification offered by M.H. Abrams (1971), Northrop Frye (2007), Yoseph Yapi Taum (2017), and Vincent B. Leitch (Veeser, 2021). Through a formal study of reading modalities (coverage, access relation, and semantic modality), a classification of critical approaches is obtained, modelled in the axis of reading: the axis of depth, width, and distance by which the critics approach the literary phenomena. Based on that model, the entire approach to literary criticism can be classified into eight octants of the cube of reading: narrow–close–surface reading, narrow–close–deep reading, narrow–distant–deep reading, narrow–distant–surface reading, wide–close–surface reading, wide–close–deep reading, wide–distant–deep reading, and wide–distant–surface reading. Each approach is positioned relationally with other approaches in the cube of reading, so the space for dialogue and comparison is always wide open. By demonstrating the morphological relationships between critical approaches, this research opens new possibilities for interpreting each critical position as a liminal one so that each position is always related to and transformed into another.